2022
DOI: 10.1177/14779714221082691
|View full text |Cite
|
Sign up to set email alerts
|

Part-time adult students’ satisfaction with online learning during the COVID-19 pandemic

Abstract: Introduction: The COVID-19 pandemic resulted in many tertiary institutions switching overnight from taught to online lectures without much preparation. Studies suggest that the sudden change has impacted on students’ satisfaction with online learning in differing ways. Yet, little is known about how this change impacted specifically on adult part-time students, which is the focus of this study. Methods: Part-time adult undergraduate students responded to a mixed methods online questionnaire. Close-ended questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Gender and sex disaggregated data have been signalled as critical aspects to ensuring gender equality [ 50 – 53 ]. Given the known additional burden that women face outside the work environment, this may hinder their possibilities for remote education [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender and sex disaggregated data have been signalled as critical aspects to ensuring gender equality [ 50 – 53 ]. Given the known additional burden that women face outside the work environment, this may hinder their possibilities for remote education [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whilst some sectors only made use of remote working towards the beginning of the pandemic and again when COVID-19 case numbers were particularly high, previous findings indicated that organisations in the studied sector made use of remote working throughout the first year of the pandemic 24) . The tool, which was tested amongst a small group of IT workers prior to distribution (n=5), contained the following measures: Proportion of remote working: A single-item question 25) asked participants to estimate their average use of remote working during the first 12 months of the COVID-19 pandemic on a 5-point scale ranging from no remote working (0%) till all of the work was done by remote working (100%).…”
Section: Methodsmentioning
confidence: 99%
“…Proportion of remote working: A single-item question 25 ) asked participants to estimate their average use of remote working during the first 12 months of the COVID-19 pandemic on a 5-point scale ranging from no remote working (0%) till all of the work was done by remote working (100%).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to quantify the percentage of work carried out via teleworking (Fiorini et al, 2022). Results were dichotomized for the purpose of analysis; some work to half of the work tasks (1), most to all work tasks (2).…”
Section: Methodsmentioning
confidence: 99%